Comparative characteristics of the transcriptional activity of CDH1, CTNNB1 genes and the expression levels of E-cadherin, β-catenin proteins, coded by these genes, in intestinal-type gastric adenocarcinoma - V. A. Tumanskiy; T. A. Khrystenko (Zaporozhye State Medical University, 2017)
Molecular genetics abnormalities, underlying aberrant expression of E-cadherin and β-catenin in malignant tumors, are still unclear. Aim: to compare the mRNA expression levels of CDH1 and CTNNB1 genes and the immunohistochemical expression levels of E-cadherin and β-catenin proteins in intestinal-type gastric adenocarcinoma. Materials and methods. The molecular genetic (real-time PCR) and immunohistochemical studies of the intestinal-type gastric adenocarcinoma (30 patients; I, II and III clinical stages were included) and of the normal stomach mucosa (10 samples) were conducted. Results. In comparison with the normal stomach mucosa, the intestinal-type gastric adenocarcinoma differs by the reduced transcriptional activity of the CDH1 gene [Me of relative normalized ratio of mRNA expression level is 0.14 (0.03; 0.40)], which correlates with the low expression level of E-cadherin in cancer cells [Me is 27,59 CUOD (23,14; 37,19), Spearman's correlation coefficient = 0,73], and also by the heightened transcriptional activity of the CTNNB1 gene [Me of relative normalized ratio of mRNA expression level is 4.32 (2.11; 11.43)], which correlates with the high expression level of β-catenin in cancer cells [Me is 116.65 CUOD (110.34; 151.32), Spearman's correlation coefficient = 0,94]. There is a reverse correlation between the CDH1 mRNA expression level and the degree of histological differentiation of intestinal-type gastric adenocarcinoma (correlation coefficient γ = -0,44); there is a direct correlation between the CTNNB1 and CDH1 mRNA expression levels (only for the I clinical stage cases); there are a direct correlations between the E-cadherin and β-catenin expression levels, and also between the CTNNB1 mRNA expression level and the E-cadherin expression level (only for the I-II clinical stage cases). Conclusion. The data indicate that decrease of transcriptional activity of the CDH1 gene and E-cadherin expression level, and also increase of transcriptional activity of the CTNNB1 gene and β-catenin expression level in the cancer cells play a critical role in the process of progression of intestinal-type gastric adenocarcinoma. gastric cancer; adenocarcinoma; CTNNB1 protein; human; CDH1 protein; human; beta Catenin; E-Cadherin